Resolving fusilier puzzles: The identity of Squamosicaesio marri and Pterocaesio flavifasciata , and a new record of Flavicaesio suevica from the Western Indian Ocean - Chinmay Kar; Rajeev Raghavan; Ameen Ummath; Naseeba Puthiyaalikom; Konham Kakkada Idreesbabu; Sivanpillai Sureshkumar (Journal of Fish Biology, 2024)
A phylogenetic analysis incorporating mitochondrial cox1 gene sequences of members of the family Caesionidae revealed the conspecificity of Pterocaesio flavifasciata and Squamosicaesio marri , which was also supported by the absence of any clear morphological diagnostic characters and meristic counts to separate the two species. Additionally, we provide the first record of the Suez fusilier, Flavicaesio suevica , from outside the Red Sea, based on specimens collected from the Laccadive archipelago, Western Indian Ocean. Together, these results show that the taxonomy, diversity, and distribution of members of the family Caesionidae continue to be poorly known, necessitating a comprehensive range‐wide study.